Essays by Roger Casement, including newspaper cuttings relating to his life and death - Casement, Roger, 1864-1916 (1907)
Essays entitled ‘Englands’ Starvation of Germany’, ‘Freedom of the Seas’ and ‘The Story of Findlay’s attempt to capture me’.
Inscribed on envelope: “Newspaper cuttings and notes / from R. [Roger Casement]".
Keywords: Casement, Roger, -- 1864-1916; Casement, Roger, -- 1864-1916 -- Death and burial; Casement, Roger, -- 1864-1916 -- Trials, litigation, etc; Findlay, Mansfeldt de Cardonnel, -- Sir, -- 1861-1932; Ireland -- History -- 1901-1910; Ireland -- History -- 1910-1921; Ireland -- Politics and government -- 1901-1910; Ireland -- Politics and government -- 1910-1921